Beyond policy positions: How party type conditions programmatic responses to globalization pressures - Onawa Promise Lacewell (Party Politics, 2017)
Do parties adapt their programmatic strategies in times of heightened economic globalization? Are these changes captured by right-left positional changes or do parties go beyond policy shifts and enact more comprehensive programmatic overhauls? Furthermore, are such changes linked to traditional party family classifications and, if so, do different party types re-program their manifestos differently? Finally, what role does radical right competition play in the changing programmatic strategies of mainstream centre-right and centre-left parties? This paper addresses these questions by developing a theoretical framework that accounts for economic globalization, cleavage change, and programmatic supply. Using Giebler et al.'s (2015) measure of programmatic clarity, the analysis reveals clear differences in party responses to economic globalization. Additionally, the results show that parties go beyond right-left positional changes and adapt their programmatic supply on a more general level. For social democratic parties, however, such adaptation hinges on whether a radical right competitor is present.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; comparative politics; party manifestos; political parties